New species of glass knifefish Eigenmannia loretana (Gymnotiformes: Sternopygidae) from the Western Amazon - Waltz, Brandon T.; Albert, James S. (Zootaxa, 2018)
A new species of the Eigenmannia trilineata species group is described from the Loreto, Peru region of the western Amazon basin. The new species is similar in external appearance to members of the E. trilineata species group, but has a distinct phenotype, being diagnosed from congeners by the following unique combination of characters: four longitudinal dark pigment stipes on the lateral surfaces (over the lateral line, hypaxial muscles, proximal and distal pterygiophore margins); short, relatively round head (head depth 86.8–96.7% head length) with a terminal mouth; intermediate posterodorsal expansion of infraorbital bones 1+2 (60–75% length of infraorbitals 1+2); 11–15 teeth in three rows on the premaxilla; six to seven teeth in a single row on the endopterygoid; eye high on head (suborbital depth 28–36% head length); ii, 13–14 pectoral-fin rays; 183–219 anal-fin rays; and a uniformly dark brown head and pectoral fins on freshly-preserved specimens. The new species extends the geographic range of described species of the E. trilineata species group to the Western Amazon. This new species elevates the current number of valid species within the E. trilineata species group to 15, and the number of species within Eigenmannia to 20.